Research on Tooth Surface Design of Curved Tooth Face Gear based on Cylindrical Gear Addendum Modified - Yong Chen; Zhanrong Feng; Yulong Zhao; Ning Huang; Lingfeng Gao; Guangjin Xiong (Jixie chuandong)
Face gear is a new gear transmission form in which involute cylindrical gear and approximate bevel gear mesh with each other. The curved tooth face gear uses the involute arc tooth cylindrical gear as the face gear formed by the imaginary tool envelope. The working tooth surface equation of the face gear is derived， and the fillet modification design of the tooth tip of the cylindrical gear is carried out. Cross-section fillet equation， fillet surface equation， and modified curved tooth surface transition surface equation are deduced， and the mathematical model of the two kinds of tooth tip cylindrical gears is established by Matlab. It is found that the tooth thickness of the face gear generated by the top fillet envelope is larger than that of the face gear generated by the top fillet envelope at the root of the inside diameter. The research results show that rounding the tool tooth tip can not only avoid the contact of the face gear and the cylindrical gear edge causing the face gear tooth surface wear，but also increase the thickness of the tooth root of the inner diameter of the face gear. This type of face gear modification also provides a theoretical basis for other tooth profile face gears.